Pemblokiran Pengusaha Ekonomi Digital Atas Cross-Border Transaction Sebagai Upaya Perubahan Skema PPN - Otto Abri Pardomuan; Suparna Wijaya (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2022)
The digital economy, which has been improving every year, has created various challenges for tax authorities, one of which is to maximize the potential for VAT. This study aims to determine the government's efforts in determining digital service providers domiciled abroad to establish a Permanent Establishment in Indonesia (BUT). Because with a PE, the PPh will become a tax subject and on a VAT basis will be a Taxable Entrepreneur (PKP). The research method used is descriptive qualitative. The results of the study show that digital economy services in Indonesia are an object of VAT and in recent years have been subject to VAT. The scheme for imposing VAT on digital-based service providers who are domiciled abroad is currently ineffective because the tax authorities' authority is very limited in conducting supervision. The government has issued a number of regulations to expand the requirements for determining the status of BUT, but in general the determination of the status of the Permanent Establishment cannot be realized, because it still requires further supporting regulations which have not been regulated until now.